A study on the figure drawing of local historical comics / Mohamad Akmal Ariff Kamarudin - Kamarudin, Mohamad Akmal Ariff (2014)
The current historical story, there are only few Malaysian public literature that be deliver in comic style. By referring to story book with long essay, it's difficult to imagine or deliver the information and need more understanding and concentration from the user. In a comparative study between comics and text, W. W. D. Sones (1944), professor of Pittsburgh University, found that,"Comics' visual quality increases learning". He noted that students of'low and middle intelligence levels" were especially helped by comics' visual quality. Furthermore, with a comic in Malay historical story, user or viewer can see the illustration and detail figure drawing also can understand the story line better then read long essay historical story book. Usually local conic is not drawn in the same style like X-men, Batman, Superman (DC and Marvel comic). Mostly there have a same element in local comic that could relate to manga style especially on its figure drawing like its muscle, eyes, and sound effect. Most of local comic artist noAvadays couldn't get their identity of it stroke drawing style and usually used the same concept that could relate to manga conic especially in the process of developing characters. Peoples can't identify the characters in term of their race and culture. For example in character of Malay soldier in conic oi^Dokumen 136", the character faces are not reflect to the faces of real Malay, Chinese and Indian people. In general, most local comic artist not able to draw the detail human figure, this because maybe they not enough in learned anatomy for figure drawing or do research. The detailing on figure drawing in conic is so important, it can make the story more interesting and not bored to read.